Competencias académicas de ciencias sociales y su relación con el nivel socioeconómico de los estudiantes del cuarto grado de secundaria de la I.E. N° 601582 Agustín Rivas Vásquez, Tamshiyacu 2024 - Garcia Arevalo, Erika Ibeth (2025)
The Thesis called: “Academic competencies in social sciences and their relationship with the socioeconomic level of students in the fourth grade of secondary education at the I.E. No. 601582 Agustín Rivas Vásquez, Tamshiyacu 2024.” This thesis developed two study variables such as academic competencies in social sciences and the socioeconomic level of the students; aiming at the statistically significant relationship between them. 73 students from two sections of the fourth grade of secondary education “A” and “B” of the I.E. participated in this thesis. N° 601582 Agustín Rivas Vásquez, likewise, the socioeconomic evaluation research instrument and the average grade of the last two months were applied. Highlighting the descriptive results such as: the average grade of the competencies in social sciences as follows: 63,0% with grade “A”, 19,2% with grade “AD”, 12,3% with grade “B”, and 5,5% with a “C” grade. And, with regard to socioeconomic level, the following results was obtained: 61.6% with a medium socioeconomic level, 30.1% with a low socioeconomic level, and 8.2% with a high socioeconomic level. That, when cross-referencing variables to determine the degree of statistical relationship with the Pearson Chi Square test, the following result was obtained: asymptotic significance of 0.388, which compared to a P value of 0.05, is higher than the level ofsignificance. Therefore, there is no statistically significant relationship, both variables are independent.